Uncertainty Analysis of Axial Pile Capacity in Layered Soils by the Piezocone Penetration Test - Lin, Jun; Hou, Xinyu; Cai, Guojun; Liu, Songyu (Frontiers in Earth Science, 2022)
This paper presented a framework for uncertainty analysis of the ultimate axial bearing capacity of piles evaluated by the Unicone method in layered soils. The UniCone method by Eslami and Fellenius (1997) is a direct piezocone penetration test (CPTU) method for evaluating the ultimate axial capacity of piles in the reliability design. The spatial variability of CPTU data is modeled as a random field for each soil unit in the soil strata. The empirical correlation coefficients of the Unicone method are assumed to follow lognormal distributions. On the basis of uncertainties of CPTU data and empirical correlation coefficients, the first-order reliability method (FORM) is then applied to the reliability analysis of ultimate axial bearing capacity of piles. The effects of spatial variability of CPTU data and variations of empirical correlation coefficients on the ultimate axial bearing capacity of piles are evaluated by an Excel spreadsheet-based framework. Seven case studies show that the proper identification of different soil units from soil profiles is crucial for estimating the failure probability of pile capacity in the reliability analysis. Uncertainties of CPTU data and empirical correlation coefficients would be over-estimated unless different soil units in soil profiles are identified properly from each other. The over-estimated geotechnical parameters contribute to a higher failure probability of pile capacity. The proposed framework can evaluate the uncertainty of the ultimate axial bearing capacity of pile foundations more rationally.